Elevated LDL-Cholesterol level predicts diabetes in centrally obese women but not men - Relative roles of insulin resistance and central obesity - Onat, Altan; Hergenq, Guelay; Sari, Ibrahim; Karabulut, Ahmet; Can, Guenay (JAPANESE CIRCULATION SOC, 2007)
Background The aim was to investigate the sex-specific effect of hypercholesterolemia interacting with abdominal obesity (AO) in predicting Type 2 diabetes mellitus (DM). The 3,048 participants (aged :28 years) were free of DM at baseline, a representative sample of Turkish adults and were evaluated prospectively. Methods and Results As cut-off points for AO were used >= 95 cm in men and 91 cm in women, and for hypercholesterolemia >= 5.2 mmol/L. Diabetes was diagnosed using criteria of the American Diabetes Association. Four groups were formed at baseline: Group I subjects had neither AO nor hypercholesterolemia (33.3%), Group It subjects had AO only (27.6%), Group M subjects had hypercholesterolemia only (17.8%), and Group IV subjects had AO combined with hypercholesterolemia (21.3%). Over a mean of 5.9 years, DM developed in 103 women and 116 men. An age-adjusted relative risk (RR) by logistic regression for DM in the 4 groups, using AO as a reference group, disclosed an RR of 1.88 (95% confidence interval 1.14; 3.09) in women and an insignificant RR 1.29 in men (women were predicted to be 1.46 times more likely to develop DM). Hypercholesterolemia alone did not differ significantly from Group I in its ability to predict diabetes. An elevated level of low-density lipoprotein (LDL) -cholesterol (C) ( >= 3.4mmol/L) was delineated as the element associated with diabetes in hypercholesterolemia by multiple logistic regression. The identification of 48 participants with familial-combined hyperlipidemia phenotypes alone could not account for most of the centrally obese and hypercholesterolemic women developing DM. Conclusion It was suggested that a diminished effectiveness of insulin resistance in centrally obese Turkish women (but not men) might predispose them to an elevation in LDL concentrations, while other features of visceral adiposity still predispose them to DM. In summary, an elevated LDL-C level interacts with AO in Turkish women to enhance the development of diabetes.
Keywords: abdominal obesity; diabetes type 2; familial-combined hyperlipidemia; hypercholesterolemia; insulin resistance; sex difference; FAMILIAL COMBINED HYPERLIPIDEMIA; DISEASE RISK-FACTORS; METABOLIC SYNDROME; CARDIOVASCULAR-DISEASE; GLUCOSE REGULATION; PLASMA-LIPIDS; MELLITUS; LIPOPROTEIN; ADULTS; Cardiovascular System & Cardiology